Neonatal Graves' Disease with Maternal Hypothyroidism - Akangire, Gangaram; Cuna, Alain; Lachica, Charisse; Fischer, Ryan; Raman, Sripriya; Sampath, Venkatesh (American Journal of Perinatology Reports, 2017)
Neonatal Graves' disease presenting as conjugated hyperbilirubinemia is a diagnostic challenge because the differential includes a gamut of liver and systemic diseases. We present a unique case of neonatal Graves' disease in a premature infant with conjugated hyperbilirubinemia born to a mother with hypothyroidism during pregnancy and remote history of Graves' disease. Infant was treated with a combination of methimazole, propranolol, and potassium iodide for 4 weeks. Thyroid function improved after 8 weeks of treatment with full recovery of thyroid function, disappearance of thyroid-stimulating antibodies, and resolution of failure to thrive and conjugated hyperbilirubinemia. This case provides several clinical vignettes as it is a rare, severe, presentation of an uncommon neonatal disease, signs, symptoms, and clinical history presented a diagnostic challenge for neonatologists and endocrinologists, normal newborn screen was misleading, and yet timely treatment led to a full recovery.
Keywords: cholestasis; failure to thrive; hyperthyroidism; Graves' disease